MySQL crash course - Forta, Ben (Sams, 2005)
MySQL is one of the most popular database management systems available, powering everything from Internet powerhouses to individual corporate databases to simple end-user applications, and everything in between. And this book will teach you all you need to know to be immediately productive with MySQL. By working through 30 highly focused hands-on lessons, your MySQL Crash Course will be both easier and more effective than you'd have thought possible. Learn how to: Retrieve and sort data Filter data using comparisons, regular expressions, full text search, and much more Join relational data Create and alter tables Insert, update, and delete data Leverage the power of stored procedures and triggers Use views and Cursors Manage transactional processing Create user accounts and manage security via access control Ben Forta is Macromedia's Senior Technical Evangelist, and has almost 20 years of experience in the computer industry in product development, support, training, and product marketing. Ben is the author of the best-selling Sams Teach Yourself SQL in 10 Minutes (now in its third edition, and translated into over a dozen languages), ColdFusion Web Application Construction Kit , and Advanced ColdFusion Development (both published by Que Publishing), Sams Teach Yourself Regular Expressions in 10 Minutes , as well as books on SQL, Flash, JSP, HomeSite, WAP, Windows 2000, and other subjects.